2004
DOI: 10.1055/s-2004-823114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Nitroglycerine on the Survival of Ischemic Flow-Through Venous Flaps in Rabbits

Abstract: The purpose of this study was to investigate the effect of transdermal nitroglycerin on the survival of an ischemic one-vein flow-through venous flap (FTVF) model in the rabbit ear. Fifteen New Zealand white male rabbits were randomly divided into three groups: Group 1 (n = 5, 10 flaps)- no dressing on the operative wound; Group 2 (n = 5, 10 flaps)-occlusive film dressing group [polyurethane semipermeable membrane (Op-Site)]; and Group 3 (n = 5, 10 flaps)- transdermal nitroglycerine pad (Novartis-Nitroderm TTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The last issue to be considered is the dosage of the drug administered. In previous studies, nitroglycerine was applied in the form of patches 4,5,18,22 and ointments. 7,13,37 While the dosage of the drug in grams was stated in the studies using the patch form, exact weight in grams was not mentioned in studies using the ointment form, probably due to difficulties in calculating the exact amount.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The last issue to be considered is the dosage of the drug administered. In previous studies, nitroglycerine was applied in the form of patches 4,5,18,22 and ointments. 7,13,37 While the dosage of the drug in grams was stated in the studies using the patch form, exact weight in grams was not mentioned in studies using the ointment form, probably due to difficulties in calculating the exact amount.…”
Section: Discussionmentioning
confidence: 99%
“…Many subsequent experimental studies confirmed this finding. [4][5][6][7] These experimental studies were followed by clinical studies and small case series that observed the benefit of nitroglycerin treatment for hypospadias treatment and peripheral necrosis. 8,9 Today, topical nitroglycerin treatment is frequently used to increase the survival of mastectomy flaps and relevant studies are ongoing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation